2013
DOI: 10.1016/j.conb.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the genetics of speech and language

Abstract: Researchers are beginning to uncover the neurogenetic pathways that underlie our unparalleled capacity for spoken language. Initial clues come from identification of genetic risk factors implicated in developmental language disorders. The underlying genetic architecture is complex, involving a range of molecular mechanisms. For example, rare protein-coding mutations of the FOXP2 transcription factor cause severe problems with sequencing of speech sounds, while common genetic risk variants of small effect size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 104 publications
2
117
0
2
Order By: Relevance
“…1,2 However, most of the genetic determinants of higher cognitive functions including learning, attention, memory and executive function remain unknown. 3,4 Working memory (WM) is a neural system that provides temporary active maintenance of necessary information while performing complex cognitive tasks such as reasoning, learning, understanding, thinking, decision making, and planning. [5][6][7] Although selective WM deficit is a rare condition, many studies have shown that poor WM performance can have an impact on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, most of the genetic determinants of higher cognitive functions including learning, attention, memory and executive function remain unknown. 3,4 Working memory (WM) is a neural system that provides temporary active maintenance of necessary information while performing complex cognitive tasks such as reasoning, learning, understanding, thinking, decision making, and planning. [5][6][7] Although selective WM deficit is a rare condition, many studies have shown that poor WM performance can have an impact on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…A framework for bridging the gap between genetics and behavior is provided by a decade of research into FOXP2 (Fisher and Scharff 2009;Graham and Fisher 2013). It is still not fully understood why disruption of one copy of this gene should lead to a severe speech and language disorder, but considerable progress has been made in elucidating both molecular-level effects and consequences for higher-level brain function.…”
Section: Epilepsy-aphasia Spectrum Disordersmentioning
confidence: 99%
“…There is evidence that these substitutions affect target regulation and synaptic plasticity, but the molecular mechanism of these effects is still unknown (Konopka et al 2009;Enard et al 2009;ReimersKipping et al 2011). Interestingly, a selective sweep may have occurred at the FOXP2 locus within the last 200,000 years, but is not explained by the amino acid substitutions and may instead relate to non-coding changes affecting FOXP2 regulation, or may be a false-positive finding (Coop et al 2008;Maricic et al 2013;Graham and Fisher 2013).…”
Section: Epilepsy-aphasia Spectrum Disordersmentioning
confidence: 99%
“…Thus, the identification of FOXP2 may have been something of a paradigm shift for the language sciences because it facilitated a series of innovative molecular investigations into the neurobiological pathways and evolutionary history of spoken language using this gene as a unique entry point (Fisher & Scharff, 2009). Such work has called on a diverse array of experimental strategies and model systems, ranging from neuronal cells investigated at a laboratory bench, to genetic manipulations in animals, to studies of humans (Graham & Fisher, 2013).…”
Section: Functions Of Foxp2: the View From The Benchmentioning
confidence: 99%
“…Arguments for a genetic basis have drawn from an array of diverse fields and approaches, marshaling threads of evidence taken from formal linguistics, child development, twin studies, biological anthropology, comparative psychology, and so on. In recent years, through advances in molecular biology techniques, it has become possible to move beyond these indirect sources and let the genome speak for itself (Graham & Fisher, 2013). In particular, by studying neurodevelopmental disorders that disproportionately disturb speech and language skills, researchers started to identify individual genes that may be involved in the relevant neurobiological pathways.…”
Section: Introductionmentioning
confidence: 99%